"Avoid that pornographic playground": Teaching pornographic abstinence in The Church of Jesus Christ of Latter-day Saints. (August 2015) - Edward Sumerau, J; Cragun, Ryan T
In recent years, many studies have examined conservative Christian responses to shifting societal attitudes about sexuality. In this article we examine official discourse from the LDS Church found in General Conference talks and the official adult magazine of the Church, Ensign, to better understand how leaders of the religion have taught the members to abstain from the use of pornography. Using a grounded-theory approach, we noted a pattern to the lessons that included four elements: (1) avoiding dangerous associations, (2) taking personal responsibility, (3) maintaining inner purity, and (4) seeking spiritual treatment. This study extends previous research by examining how Mormon leaders taught their followers to interpret and protect themselves from pornography. As such, our analysis demonstrates the elaboration of religious teachings that may facilitate the negative reactions to pornography researchers have observed in survey and outcome-based research on members of conservative religions.